CPLX1 is a novel prognostic biomarker in CRC correlating with immunotherapy resistance and ferroptosis - Liu, Canyu; Liu, Qiujun; Lv, Yuanhao; Chang, Tingmin; Song, Shiyi; Ding, Yuang; Zhong, Jiateng; Liu, Yanxuan (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) remains a predominant contributor to cancer-related mortality globally, with its resistance to immunotherapeutic strategies presenting a formidable challenge in patient management. Recent investigations have illuminated the prospective involvement of ferroptosis, a regulated form of cell death, in both cancer progression and the development of resistance to therapeutic interventions.ObjectiveThis study aims to elucidate the prognostic significance of CPLX1 in CRC, specifically its correlation with immunotherapy resistance and its association with ferroptosis, thereby contributing to a deeper understanding of tumor biology and therapeutic vulnerability.MethodsWe conducted an integrative analysis of RNA-seq datasets from the TCGA-COAD and TCGA-READ projects, along with the GEO GSE156451 dataset, to discern differentially expressed genes. Expression levels of CPLX1 were evaluated utilizing the TIMER 2.0 database, and survival analyses were performed via Kaplan-Meier plots and Cox regression modeling to assess prognostic implications. Additionally, mutational analyses through cBioPortal and COSMIC datasets were employed to identify CPLX1 mutations in COAD. Co-expression and functional enrichment analyses, alongside Gene Set Enrichment Analysis (GSEA), were also conducted to delineate pathways impacted by CPLX1.ResultsOur findings indicate that high expression levels of CPLX1 are significantly correlated with poor prognostic outcomes in CRC patients. Through immune infiltration analyses employing ssGSEA, we observed notable associations between CPLX1 expression and specific immune cell populations. Furthermore, the interaction between CPLX1 and ferroptosis-related genes suggests a potential mechanistic linkage that could underpin therapeutic resistance.ConclusionCPLX1 is identified as a novel prognostic biomarker in CRC, exhibiting clear correlations with both immunotherapy resistance and ferroptosis. These findings indicate that targeting CPLX1 may provide novel therapeutic strategies to ameliorate treatment resistance in CRC.